Selenium-Binding Protein 1 expression in ovaries and ovarian tumors of in the laying hen, a spontaneous model of human ovarian cancer - Stammer, Karen (2008)
OBJECTIVE: Reduced Selenium-Binding Protein 1 (SELENBP1) expression was recently shown in multiple cancers. There is little information on the expression and function of SELENBP1 in cancer progression. In order to develop a better understanding of the role of SELENBP1 in ovarian cancer, our objective was to determine if SELENBP1 is expressed in the normal ovaries and ovarian tumors in the egg-laying hen, a spontaneous model of human ovarian cancer. METHODS: SPB1 mRNA expression in normal ovary (n=20) and ovarian tumors (n=23) was evaluated by RT-PCR. Relative levels of mRNA were compared by quantitative RT-PCR (qRT-PCR) in selected samples. SELENBP1 protein expression was evaluated by 1D Western Blot and immunohistochemistry with a commercial anti-human SELENBP1 antibody. RESULTS: SELENBP1 mRNA and protein was expressed in 100% of normal and ovarian tumors and qRT-PCR confirmed decreased mRNA expression in 80% of ovarian tumors. SELENBP1 was primarily localized in surface epithelial cells of normal ovaries. In ovaries containing early tumor lesions, SELENBP1 expression was reduced in the surface epithelium near the tumor and was expressed in tumor cells, while more distant regions with normal histology retained SELENBP1 expression in the surface epithelium. CONCLUSIONS: We have shown for the first time that SELENBP1 is expressed in both normal ovaries and ovarian tumors in the hen and that SELENBP1 expression is altered in the vicinity of the tumor. Furthermore, SELENBP1 expression in normal ovarian surface epithelium and in ovarian tumors parallels that previously reported for ovarian cancer in women.